The development of maize seed markets in Sub-Saharan Africa - Rusike, Joseph (International Food Policy Research Institute, 1995)
The development of the maize seed industry and private seed companies in selected Sub-Saharan Africa countries over the past 95 years is outlined. The study provides evidence that seed industry development is an evolutionary learning-by-doing process of fitting together a set of interactive and mutually supporting institutions in a path dependent way that hold down transaction and production costs and infuse trading confidence in seed transactions. The government has a critical role to play in crafting and enforcing seed laws and regulations because it is ultimately the state that determines when standards are broken and whether penalties should be imposed on violators. Although the ultimate effects of structural adjustment programs on the seed industry in Southern Africa are unknown at this time, the programs have encourage multinational seed companies to enter the seed markets of South Africa, Zimbabwe, Zambia, Malawi, Kenya and Tanzania. However, there are country-specific legal and regulatory hurdles that need to be overcome if structural adjustment programs are to achieve their full potential in improving the economic performance of the seed markets.